Current and novel BTK inhibitors in Waldenström's macroglobulinemia. (February 2021) - Ntanasis-Stathopoulos, Ioannis; Gavriatopoulou, Maria; Fotiou, Despina; Dimopoulos, Meletios A.
The current therapeutic approach in Waldenström's macroglobulinemia (WM) is being driven by insights in disease biology and genomic landscape. Bruton's tyrosine kinase (BTK) plays a key role in signaling pathways for the survival of WM clone. BTK inhibition has changed the treatment landscape of the disease. Ibrutinib has resulted in deep and durable responses both as an upfront and salvage treatment with a manageable toxicity profile. However, the need for fewer off-target effects and deeper responses has resulted in the clinical development of second-generation BTK inhibitors. Zanubrutinib has resulted in clinically meaningful antitumor activity, including deep and durable responses, with a low discontinuation rate due to treatment-related toxicities. Cardiovascular adverse events seem to be milder compared with ibrutinib. Interestingly, the efficacy of zanubrutinib in WM is significant both for MYD88 L265P and MYD88 WT patients. Although the randomized, phase III ASPEN clinical trial did not meet its primary endpoint in terms of showing a superiority of zanubrutinib in deep responses compared with ibrutinib, secondary efficacy and safety endpoints underscore the potential clinical role of zanubrutinib in the treatment algorithm of WM independent of the MYD88 mutational status. Combination regimens and non-covalent BTK inhibitors are emerging as promising treatment strategies. Long-term data will determine whether next-generation BTK inhibitors are more potent and safer compared with ibrutinib, and whether they are able to overcome resistance to ibrutinib, either alone or in combination with inhibitors of other interrelated molecular pathways.